The Role of Retail Sukuk in Development and Investment Financing: Ibn Khaldun's Perspective in the State Economy - Wafa, Fadhil; Maulidia, Rohmah (Pt. Anagata Sembagi Education, 2024)
This article examines the role of retail sukuk as a sharia financial instrument in supporting development and investment financing, by integrating the perspective of Ibn Khaldun's economic thought. Retail sukuk functions as an alternative financing that involves direct community participation, while supporting the realization of sustainable development projects, such as infrastructure, education, and health. In Ibn Khaldun's view, a country's economic development requires a balance between the role of the government and community contributions. The principles of justice and transparency inherent in retail sukuk are in line with the concept of wealth distribution and inclusive economic management in Ibn Khaldun's theory. This article also highlights how the implementation of retail sukuk can encourage economic growth, expand the investor base, and create social stability through a more equitable distribution of benefits. By integrating sharia principles and moral values taught by Ibn Khaldun, retail sukuk can be a strategic instrument in building a just and sustainable economy. This research offers a new perspective on the synergy between classical thinking and modern financial innovation to support national economic development.